iCalorie: BMR Calories Fitness Mobile Application - Zulkifli, Muhamad Zairi (IRC, 2019)
Obesity is a complicated disease that involves excessive body fat. Obesity is not just a matter of cosmetics. It raises your risk of illness and health issues like heart disease, diabetes, and high blood pressure. Being highly obese means that you are particularly probable to have weight-related health issues. The excellent news is that even modest weight loss can enhance or deter obesity-related health issues. Changes in diet, improved physical exercise, and changes in conduct can assist you lose weight. The problem connected with these issues is that individuals tend to find it difficult to determine calories for the food they eat, difficult to develop a comprehensive diet and fitness plan, and absence of knowledge of work on Basal Metabolic Rate (BMR). By utilizing the knowledge of current mobile application system, the author suggests to develop a mobile application that can calculate calories needed for individual and send a warning notification if the calories consume per day more than what their body required. The objective of the application is to produce a mobile phone app that calculates Basal metabolic rates and easily calibrate Malaysian meals. Develop a mobile app to create a systemic and centrally planned health and fitness program. In this project, author use the System Development Life Cycle agile methodology in order to improve in a timely manner whenever there are requirements change. So, this project assessment expected to be functioned well to user who willing to achieve their goals in fitness based on requirements gathering. This application will be using some feature testing and user acceptance test to increase user satisfaction.